The Importance of Vitamin and Mineral Intake for 12-Year-Old Child Growth - Salsabilla Martina Ayu; Asep Bayu Dani Nandiyanto (Indonesian Journal of Educational Research and Technology, 2023)
This study aims to provide an understanding of the importance of vitamins and minerals, as well as foods and drinks containing vitamins and minerals according to age. As to prevent children's growth and development disorders. The method used in this research is pre-experimental with a quantitative approach. The research was carried out at Hanjuang Samijaya Elementary School in July 2022 with a sample of 15 students. The stages of the research are pretest, socialization of the importance of vitamins and minerals for the growth of children aged 12 years, and posttest. Based on the results of the study, students' understanding of the importance of vitamin and mineral intake for the growth of 12-year-old children increased after being given socialization. The percentage of students' average N-Gain score is 60%. This indicates the socialization carried out is quite effective. This is because of the enthusiasm of students in paying attention when socialization is being held, then the information can be conveyed and understood properly. Students who previously did not know and paid less attention to the vitamins and minerals their bodies needed, became more aware of and paid attention to the importance of these things. With this research, it is hopedevery parent and child will pay attention to the intake of vitamins and minerals needed by the body. As to avoid impaired child growth and development.